Customers’ Perception on Food Hygiene and Safety at Pasar Siti Khadijah, Kota Bharu - RADEN ISMAIL, RADEN MOHD FARHAN HELMY; MAT RASOL , NUR FATIN SHAHADA; ROHIAT, MOHD AKMAL (Research and Innovation in Technical and Vocational Education and Training, 2021)
The level of hygiene and safety of food served by sellers should be taken into consideration by the buyers or customers to ensure that the food provided is safe to eat. Therefore, this study was conducted to find out the perception of society on food hygiene and safety at Pasar Siti Khadijah, Kota Bharu. In this study, the researcher focused on two aspects which are the level of food hygiene and the level of food safety. For data analysis the researcher has chosen to use the questionnaire form method. The results of this study were analyzed using software Statistical Package For The Social Science (SPSS) version 25.0. Data analysis showed that average mean values ​​were at a median level of 3.02 for food hygiene while average mean values ​​for food safety were served at a median level of 3.09.